2014
DOI: 10.4314/wsa.v40i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent sensing and determination of mercury (II) ions in water

Abstract: The presence of heavy metals released from industrial activities into water streams is an ever-growing challenge to ensuring a safe and clean aquatic environment. Detection and determination of the levels of these heavy metals in wastewater is an important step before any measures can be taken. In this study we report on a fluorescent sensing probe based on a naphthyl azo dye modified dibenzo-18-crown-6-ether (DB18C6) for the detection and determination of mercury (II) ions in water. The probe showed high sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Transition metals have also been detected using modified crown ethers. Azo dye-appended 157 (Figure ) bound to Hg 2+ and Cu 2+ with 80% and 40% quenches of emission and Stern–Volmer constants of 1.18 × 10 5 M –1 and 3.85 × 10 4 M –1 , respectively, whereas neither K + nor Na + produced notable emission changes . A detection limit of 12.5 nM for mercury was found, and this technique was applied for mercury detection in industrial water runoff from a coal-fired power plant, in which a mercury concentration of 1.64 μM was determined.…”
Section: Luminescent Macrocycle Sensorsmentioning
confidence: 99%
“…Transition metals have also been detected using modified crown ethers. Azo dye-appended 157 (Figure ) bound to Hg 2+ and Cu 2+ with 80% and 40% quenches of emission and Stern–Volmer constants of 1.18 × 10 5 M –1 and 3.85 × 10 4 M –1 , respectively, whereas neither K + nor Na + produced notable emission changes . A detection limit of 12.5 nM for mercury was found, and this technique was applied for mercury detection in industrial water runoff from a coal-fired power plant, in which a mercury concentration of 1.64 μM was determined.…”
Section: Luminescent Macrocycle Sensorsmentioning
confidence: 99%
“…K + , Li + , Na + , Ag + , Ca 2+ , Mg 2+ , Ba 2+ , Sr 2+ , Ni 2+ , Co 2+ , Cd 2+ , Pb 2+ , Cu 2+ , Fe 3+ , Al 3+ , La 3+ , Eu 3+ and Dy 3+ ) has been reported in literature. 22,23 In this work, cadmium(II) and Pb(II) ions were chosen for the selectivity studies using UV visible and uorescence spectroscopy because of the similar chemical properties between Cd(II), Pb(II) and Hg(II) and the fact that these toxic heavy metals are among the commonly known environmental pollutants. The UV absorption (Fig.…”
Section: Selectivity Of Adb18c6 Crown Ether Towards Hg(ii)mentioning
confidence: 99%
“…[19][20][21] The selective complexation of Hg(II) over a wide range of environmentally relevant metal ions by dibenzo 18-crown-6 azo dye derivatives using UV-visible and uorescence spectrometry has been reported in the literature. [22][23][24] In this work, a different mode of detection (i.e. SERS) with high sensitivity and a new aminodibenzo-18-crown-6 (ADB18C6) derivative was used.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that photoinduced electron transfer between metal ion and organic ligand. 55,56 Then, to a red solution of PBC in PSS Cu 2+ or Hg 2+ ions was added. The red solution could also immediately bleach aer adding Cu 2+ or Hg 2+ ions.…”
Section: Resultsmentioning
confidence: 99%